First recognition of a Laurentide Ice Stream : Robert Bell on Hudson Strait - Brookes, Ian (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractIn papers published in 1895 and 1901, and in undated notes for a 1907 paper he did not deliver or publish, Robert Bell of the Geological Survey of Canada interpreted the pattern of glacial striae, stossing of rock knobs, and surficial sediment composition along the margins of Hudson Strait, between Labrador, Ungava Bay and Baffin Island, as evidence of what he called an ice-stream, a long river-like glacier, fed from Hudson Bay and Foxe Basin, that had moved eastward along the Strait during the Late Glacial period. This was the earliest mention of such a glaciological feature within the Laurentide Ice Sheet (LIS). It was not until ice-streams were recognized in the West Antarctic Ice Sheet in the 1970’s that Bell’s concept was revived in the next decade and subsequently, in recognition of several ice-streams within the Late Wisconsinan LIS.